Optimizing Instagram Media in Art Education as a Development Effort Community Creative in Kampung Rejomulya Semarang - Firdaus Azwar Ersyad; Kharisma Ayu Febriana; Qorinta Sinta (Universitas Negeri Semarang, 2023)
In today's digital era, social media platforms are used for various purposes, including education and community development. Instagram, a photo and video sharing platform, has gained popularity among individuals and organizations as a tool for promoting arts education and community development. This research aims to explore the potential of Instagram as a tool to improve art education and community development in the Rejomulyo village area of Semarang . This research examines the benefits of using Instagram for arts education and community development area Rejomulyo Semarang. Besides that , research This explore the practice of deep skill inheritance batik through Instagram media . Next, research it will examine strategies that can be used to ensure effective use of Instagram for arts education and community development . significance study This lies in fact empirical that Instagram has become valuable resource _ for generations _ young . With effective and efficient optimization Instagram can increase ability public For Study art education practice through develop skills batik . As for the method research used _ use design study qualitative . Whereas procedure data collection using observation , interview and study document .